Ajax in Oracle JDeveloper - Vohra, Deepak (Springer, 2017)
Asynchronous JavaScript and XML (Ajax) is a web technique used to transfer data between a browser and server asynchronously without posting the web page to the server. "Asynchronously" implies that the processing of the web page continues while the Ajax request is sent to the server and a response is received from the server. The web page, or section(s) of the web page, is refreshed with the Ajax response without reposting the web page. Ajax has the following advantages over non-Ajax web applications.